Charging Management System for Electric Vehicles considering Vehicle-to-Vehicle (V2V) Concept - Guldorum, Hilmi Cihan; Sengor, Ibrahim; Erdinc, Ozan (IEEE, 2020)
The integration of electric vehicles (EVs) into the grid has become an important topic by the widespread usage of EVs. The possible increase in demand due to EVs has become a concern. However, recent studies have shown that EVs may be beneficial in terms of grid reliability and flexibility by using charging models such as vehicle-to-grid (V2G) energy transfer, vehicle-to-home (V2H) energy transfer and vehicle-to-vehicle (V2V) energy transfer. On the other hand, these models may cause the comfort violation of EVs' owners. In this study, the effect of energy transfer between vehicles on the comfort of EV owners have been investigated. The results show that the negative effects of vehicle-to-grid energy transfer and power limit limitation applications on user comfort are reduced with the assistance of the energy transfer charging model between vehicles.
Keywords: charging management; comfort violation; electric vehicles; vehicle-to-vehicle; vehicle-to-grid; Engineering